2019
DOI: 10.1016/j.molmet.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A role for foregut tyrosine metabolism in glucose tolerance

Abstract: Objective We hypothesized that DA and L-DOPA derived from nutritional tyrosine and the resultant observed postprandial plasma excursions of L-DOPA and DA might affect glucose tolerance via their ability to be taken-up by beta cells and inhibit glucose-stimulated β-cell insulin secretion. Methods To investigate a possible circuit between meal-stimulated 3,4-dihydroxy-L-phenylalanine (L-DOPA) and dopamine (DA) production in the GI tract and pancreatic β-cells, we: 1) mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…Functionally, we show that α-cells produce both L-DOPA and DA de novo and significantly boost DA production in response to exogenous L-DOPA supplementation. In contrast, both in vitro and in vivo studies suggest that β-cells synthesize little L-DOPA de novo but instead rely on uptake of precursors from the peripheral circulation to drive DA production 6,7,9,33,34,59 . Remarkably, after meals, blood L-DOPA and DA levels increase >50-fold in humans and rodents [67][68][69][70][71] , allowing β-cells to tune DA synthesis and signaling to meal size 7 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Functionally, we show that α-cells produce both L-DOPA and DA de novo and significantly boost DA production in response to exogenous L-DOPA supplementation. In contrast, both in vitro and in vivo studies suggest that β-cells synthesize little L-DOPA de novo but instead rely on uptake of precursors from the peripheral circulation to drive DA production 6,7,9,33,34,59 . Remarkably, after meals, blood L-DOPA and DA levels increase >50-fold in humans and rodents [67][68][69][70][71] , allowing β-cells to tune DA synthesis and signaling to meal size 7 .…”
Section: Discussionmentioning
confidence: 97%
“…We employed a CRISPR-Cas9-mediated approach to delete endogenous α 2A -adrenergic receptor expression in INS-1E cells. Since INS-1E cells are rat-derived, we used the mRNA sequence encoding rat α 2A -adrenergic receptor as a template to generate guide RNA (gRNA) to disrupt the promoter region of the Adra2a gene (gRNA sequence: 5′-GCAGCCGGATGCCGGCAATA-3′, positions [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. We then generated a construct containing the Adra2a gRNA sequence along with cDNA sequences encoding Cas9 and GFP (pENTR-Adra2a-sgRNA-Cas9-GFP).…”
Section: Generation Of α 2a -Adrenergic Receptor Knockout Cell Linementioning
confidence: 99%
“…Recent studies demonstrated that chronic administration of L-tyrosine inhibited the activity of complex I, II-III, and IV in the striatum, which can be prevented by antioxidant treatment [413,414]. Consistently, oral supplementation of L-tyrosine impairs glucose uptake and insulin secretion in rats [415], and the capacity to detoxify excess L-tyrosine is an essential life trait for the blood-sucking arthropods [416,417]. Quite interestingly, L-tyrosine was negatively correlated with hypothalamic transcriptional levels of Drd5, a dopamine receptor expressed in the limbic regions of the brain [418] that not only activates memory formation [419] but also evokes anti-tumor effects through autophagy induction [420].…”
Section: Cisand Trans-rsv Have Opposite Effects On Tyrrs-regulated Pamentioning
confidence: 90%
“…Whether dietary supplementation of tyrosine is able to modulate glucose tolerance is studied within an ongoing clinical trial [ 47 ]. A recent study in rodents showed that beta cell function is affected by oral tyrosine administration and postulated dopamine and L-DOPA derived from nutritional tyrosine as anti-incretin candidates [ 48 ]. On the one hand, high blood levels of tyrosine may result in high L-DOPA and dopamine levels and therefore strengthen the anti-incretin effect.…”
Section: Discussionmentioning
confidence: 99%